Numerical simulation of TIG weld pool dynamics using smoothed particle hydrodynamics. (December 2017) - Trautmann, M.; Hertel, M.; Füssel, U.
Highlights: A SPH-model for TIG-welding, including welding speed, temperature dependent material properties and arc influences. Surface movement due to pressure, shear, gravity, marangoni effect. Small particles and large model to reach quasi-stationary state during the welding process. Resulting welding penetration is compared to experiments with good agreement. Weld pool flow, weld pool form and temperature distribution are discussed using the model. Abstract: A three-dimensional computational weld pool model for TIG welding is described. The model is based on the smoothed particle hydrodynamics method and takes various forces in the weld pool into account including shear stress and arc pressure, surface tension, marangoni effect, gravity and the welding speed. The numerical results are compared to cross sections from experiments for different welding currents and show a very good agreement. The model is then used to describe the weld pool dynamics and the formation process of the weld penetration as well as the temperature distribution in the weld pool.